ANALISIS STATUS KEBERLANJUTAN EKOWISATA DI TAMAN NASIONAL GUNUNG RINJANI - Pipin Noviati Sadikin; Sri Mulatsih; Hadi Susilo Arifin; Bambang Pramudya Noorachmat (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2020)
Ecotourism in Mount Rinjani National Park (MRNP) faces various environmental problems that lead to conflicts. Therefore, an analysis of sustainability status of MRNP ecotourism management is carried out. The method for evaluating the sustainability status of MRNP ecotourism management is MDS (multi-dimensional scaling) with Rap-fish or Rapid Appraisal Index modified to Rap-ecotourism. The index value to determine the sustainability status is obtained from scoring value of dimensions’ attributes studied. Then, a leverage analysis is performed to observe the leverage's attributes and fall into the sensitive category as a driver for determining the sustainability of a dimension. These attributes need to be intervened by developing policies so that the index value goes into a sustainable level. The results show that the economic dimension (58.49%) is in quite sustainable level, while the ecological dimension (35.94%), social dimension (45.81%), ecotourism service dimension (39.58%), and technology and infrastructure dimension (35.29%) are in less sustainable stage. While institutional and policy dimension (23.76%) is in not sustainable status. On institutional and policy dimensions, the main lever attributes are (1) local institutions (5.53%), (2) partnerships and collaborations (5.53%), and (3) MRNP ecotourism management and control regulations (5.36%).